Sooblikovanje porodne izkušnje na podlagi reprezentacije poroda v množičnih medijih - Jurše, Ana Monika (Obzornik zdravstvene nege, 2025)
Introduction: The mass media are one of few sources of portrayals of the birthing process in women; however, these representations can also generate concern. The purpose of this study is to examine the portrayal of childbirth in the mass media, with the aim of identifying its connection to women's birthing experiences. Methods: A literature search was conducted, using the DiKUL, EBSCO Information Services, Google Scholar, ProQuest, PubMed, ResearchGate, ScienceDirect, and SpringerLink bibliographic databases with search terms in Slovenian and English. The inclusion criteria were publications from the period between 2012 and 2022 as well as content relevance and pertinence. The literature selection process followed the PRISMA guidelines. Of the initial 349 hits, 26 scientific sources were included for detailed analysis after the exclusion of duplicates and publications that did not meet the inclusion criteria and content relevance. Results: Birthing representations in the mass media can be biased and are not always evidence-based. Common and predictable patterns can be identified, most notably a dramatic portrayal of the biomedical model of childbirth that instils fear in pregnant women and leads to a preference for caesarean sections. Discussion and conclusion: Birthing representations in the mass media convey a normative view of medicalised childbirth, while alternative options are rarely and ambiguously presented. This could be significantly influenced by the collaboration between media producers and the midwifery profession. There is a lack of scientific articles on the representation of childbirth in the Slovenian context, which creates opportunities for future research and the potential for further advancement in midwifery practice and antenatal and perinatal care of expectant mothers.
Keywords: birth; javna podoba; mass media; množični mediji; nosečnost; pregnancy; public image; rojstvo